Requisites and possibilities of a controlled nationalization of agricultural policy - Ulrich Koester (Intereconomics, 1981)
The recent announcement of the French Government's decision to support the French agriculture this spring by direct income transfers to the tune of ffr 4.6 bn brings home the fact that some national governments need national autonomy in agricultural policy. Regrettably it seems to foreshadow an increasingly uncontrolled trend towards nationalization in this field. Our contributor therefore takes up the question whether the problems of the Common Agricultural Policy could not be defused by dividing the competences differently.
Keywords: 330; European Community